Transcatheter Left Atrial Appendage Closure - Gordon X. Wong; Gagan D. Singh (Methodist DeBakey Cardiovascular Journal)
Atrial fibrillation is the most common arrhythmia worldwide, placing a large population at risk for potentially disabling ischemic strokes, yet an estimated 50% of eligible patients cannot tolerate or are contraindicated to receive oral anticoagulation. Within the last 15 years, transcatheter options for left atrial appendage closure (LAAC) have provided a valuable alternative to chronic oral anticoagulation for reducing risk of stroke and systemic embolism in patients with nonvalvular atrial fibrillation. With newer generation devices such as Watchman FLX and Amulet gaining approval from the US Food and Drug Administration in recent years, several large clinical trials have demonstrated the safety and efficacy of transcatheter LAAC in a population intolerant to systemic anticoagulation. In this contemporary review, we discuss the indications for transcatheter LAAC and the evidence evaluating the use of various device therapies currently available or in development. We also examine current unmet challenges in intraprocedural imaging and controversies in postimplantation antithrombotic regimens. Several ongoing seminal trials are hoping to clarify the role of transcatheter LAAC as a safe, first-line option for all patients with nonvalvular atrial fibrillation.